An assessment of the education for all thru radio (EFAR) Program - Macalincag, Anna Leah F.; Zamora, Elvira (Quezon City University of the Philippines Diliman, 2009)
Education plays a critical role in the development of individuals and their communities. In a larger context, the educated population greatly contributes to the growth of economies through the application of skills and competencies required for sustained competitiveness through innovation. Given this, access to quality education has been widely prioritized. Related to this, enhancement of instructional approaches and educational content has been actively undertaken and closely monitored through programs that maximize the potential of economies to achieve sustainable development. The Education for All thru Radio or EFAR is one such program designed to increase access to quality education and educational services required in areas where these are not readily available. While it is a professional development program for teachers, it also serves as a non-formal training for young adults and other members of the community. Through radio, EFAR increases knowledge on Science and Math topics which may be readily applied to daily living. Aside from the radio lessons, EFAR also provided training for selected administrators and learning area supervisors who were tasked to train teachers after listening to the program. These training were conducted by participating Schools Division of the Department of Education to prepare teachers for integrating lessons into classroom instruction. Instructional materials and transcripts of radio lessons were also provided as supplements to the radio broadcasts. Lessons developed through the program were aired by partner radio stations nationwide for more than 400 teachers representing 9 Schools Divisions. The assessment of EFAR was conducted to evaluate the outcome of the EFAR pilot during SY 2007-2008. The assessment report essentially supports the endorsement of the program to the Department of Education that will lead institutional implementation following the completion of the pilot. It became imperative for the funder and the implementation team to make the endorsement to ensure nationwide adoption of the program to address the need for teacher professional development and promotion of quality education in the country. It specifically aimed to describe the components and activities of the program, identify factors that contributed to the outcome of the program and provide recommendations for enhanced administration of the program. A survey was conducted to generate information regarding the benefits and relevance of the program for teaching and the community. In addition to the survey, implementation sites were also visited to validate information provided in the survey and generate insights regarding the implementation of the program in various areas. During the interviews, feedback regarding the development of instructional materials and the conduct of classroom discussion were also generated. The results of the survey were highlighted by benefits and relevance of the EFAR radio lessons and teacher training. Teachers reported to have enhanced their knowledge on the topics discussed through the program. Participants also communicated that face to face trainings held after listening to the programs prepared them in executing suggested activities in their respective classes. It also provided opportunities for them to innovate on these activities and combine multiple approaches that increased student participation.
During the implementation of the program, participating schools divisions reported that there were signal interferences that had to be dealt with to prevent major disruptions and discontinuation of implementation activities. These were appropriately resolved in coordination with the EFAR implementation team and the broadcasting partners. As the Department of Education gears up for nationwide adoption of the program, the recommendations for enhanced program administration include : Integration of EFAR into the ICT4E program of the Department of Education. DepEd's ICT4E program aims to comprehensively integrate the use of computers, the Internet and related new technologies that would make national level instruction at par with global standards. While the use of computers and the Internet in public high schools is gradually increasing, elementary teachers and students may be involved in the program to introduce them to the use of technologies to enrich the learning process. Implementation of the EFAR program will therefore serve as the preparatory phase of the ICT4E program that will ensure successful achievement of goals and objectives set for the use of computers, the Internet and new technologies at the high school level. Integrate Planning and Management component onto the program package. The planning and management component for the program will consist of workshops conducted for school principals and division administrators. During these workshops, relevant teaching and learning issues will be defined. Based on these issues, all participating divisions will generate plans for administration of the program within their locality. This will promote ownership among stakeholders and enable them to formulate strategies that will ensure sustainability of the program. Broaden broadcasting network partnership. It is suggested that DepEd broaden its partnership with broadcasting networks beyond the existing members of the EFAR network. This will provide greater opportunities for serving other remote areas where special educational services are either scarce or unavailable. It is suggested that inter agency linkages with Radyo ng Bayan stations be established to better rationalize provision of free airtime to program beneficiaries. Integrate Face to Face training into the annual INSET Program. Every year, principals and teachers undergo the In-Service Enhancement Training (INSET) to update their instructional skills. To complement other skills learned in the previous years, the face to face training may also be integrated as one of the programs for the inset. This would be an appropriate timing for following up on and reinforcing learning from the discussions on topics aired in September. Integrate the EFAR Program into the ALS Program. During the pilot administration of the program, EFAR was not comprehensively integrated into the Alternative Learning Systems (ALS) program of DepEd because the unit was following its own curriculum. For SY 2010-2011, the integration of EFAR lessons into the ALS program is recommended primarily as a means of adding content. It may also serve as an enrichment or review course for community learners who will be taking the accreditation and equivalency exam or A&E to earn their high school diploma and be eligible for employment.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Radio programs; Education for all thru radio (EFAR) Program